2019
DOI: 10.2185/jrm.3010
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous rectus sheath hematoma associated with warfarin administration: a case report

Abstract: Objectives: Rectus sheath hematoma (RSH) can result from bleeding into the rectus abdominis muscle or a direct muscular tear; nontraumatic spontaneous RSH is a rare condition. Here, we report a case of spontaneous RSH associated with warfarin administration for the treatment of chronic thromboembolic pulmonary hypertension (CTEPH).Patient: An 87-year-old woman was referred to our hospital because of abdominal pain, nausea, and vomiting for 3 days. She was receiving warfarin for treating CTEPH. She had a bulgin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 11 publications
1
24
0
Order By: Relevance
“…RSH accounts for 1-2% of acute abdominal syndrome cases (2,5,8,11). Although its incidence is rare, certain studies have reported a high mortality rate of up to 25% with anticoagulant therapy (2,4,11,12).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…RSH accounts for 1-2% of acute abdominal syndrome cases (2,5,8,11). Although its incidence is rare, certain studies have reported a high mortality rate of up to 25% with anticoagulant therapy (2,4,11,12).…”
Section: Discussionmentioning
confidence: 99%
“…Although its incidence is rare, certain studies have reported a high mortality rate of up to 25% with anticoagulant therapy (2,4,11,12). The etiology of RSH includes trauma, intensive muscle contractions, and iatrogenic and anticoagulant therapy (2,3,5,12,13). Anticoagulant therapy is one of the major risk factors of RSH (14).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations